Results of percutaneous release of stenosing tenosynovitis (trigger finger) using hypodermic needle - Kumar, Shiv; Muzzafar, Khalid; Tasaduq, Irfan; Bijyal, Arpan (International Journal of Research in Orthopaedics, 2019)
Background: Stenosing tenosynovitis or trigger finger is a common condition affecting finger function, which can lead to disability in hand function. Treatment in form of conservative can be helpful in early stages, however later stages and chronic triggering needs release of A1 pulley either by open or percutaneous methods. The aim of this study was to find the results of percutaneous release of trigger finger with 18 guage needle. Methods: 43 digits in 36 patients were enrolled for this prospective study in a district level hospital over a 2 year period. Release was done under local anaesthesia using 18 guage needle percutaneously. Follow up was done upto 6 months. Final scoring was done at 6 months using Quinell’s criteria. Results: We had 81.39% (35 out of 43) excellent to good results. 19.61% (8) needed open release. We had no neurovascular injury or infection in our series. Conclusions: Percutaneous release by 18 guage needle is safe and effective treatment for trigger finger without much complication.